2012
DOI: 10.1016/j.epsl.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Modern seasonal variability and deglacial/Holocene change of central Arctic Ocean sea-ice cover: New insights from biomarker proxy records

Abstract: Keywords:Arctic Ocean sea ice biomarker IP 25 Younger Dryas sediment trap a b s t r a c t For the reconstruction of sea-ice variability, a biomarker approach which is based on (1) the determination of sea-ice diatom-specific highly-branched isoprenoid (IP 25 ) and (2) the coupling of phytoplankton biomarkers and IP 25 has been used. For the first time, such a data set was obtained from an array of two sediment traps deployed at the southern Lomonosov Ridge in the central Arctic Ocean at water depth of 150 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 59 publications
8
107
0
Order By: Relevance
“…Previous studies based on the analysis of IP 25 in sea ice and sediments have shown a consistent abundance relationship between these two structural homologues indicating a common source at least within the Arctic 12,24,33,34 . Our data not only confirm this source association but, the similarity of the C 25:2 /IP 25 ratio in producers (2.3 ± 0.8) to that found in sea ice and sediments 12,24,33,34 , implies a close link between the source and Arctic sedimentary signatures of these two biomarkers. As such, a significant formation of IP 25 over C 25:2 (or vice versa) in sea ice or differential degradation of either biomarker in situ, seems unlikely.…”
Section: Identification Of Ipmentioning
confidence: 99%
“…Previous studies based on the analysis of IP 25 in sea ice and sediments have shown a consistent abundance relationship between these two structural homologues indicating a common source at least within the Arctic 12,24,33,34 . Our data not only confirm this source association but, the similarity of the C 25:2 /IP 25 ratio in producers (2.3 ± 0.8) to that found in sea ice and sediments 12,24,33,34 , implies a close link between the source and Arctic sedimentary signatures of these two biomarkers. As such, a significant formation of IP 25 over C 25:2 (or vice versa) in sea ice or differential degradation of either biomarker in situ, seems unlikely.…”
Section: Identification Of Ipmentioning
confidence: 99%
“…This cold reversal was most likely initiated by a massive glacial lake drainage into the Arctic Ocean that reduced the Atlantic Meridional Overturning Circulation (Broecker, 2006;Broecker et al, 1989;Fahl and Stein, 2012;Murton et al, 2010;Stein et al, 2012;Tarasov and Peltier, 2005). Nonetheless, the influence of AW is seen at numerous locations around Svalbard, at least during the early YD and possibly temporarily (e.g.…”
Section: The Role Of Atlantic Water In the Deglaciation History Of Thmentioning
confidence: 99%
“…Brassicasterol and dinosterol were quantified as trimethylsilyl ethers using the molecular ions m/z 470 and m/z 500, respectively, in relation to the molecular ion m/z 464 of cholesterol-D 6 . For more details about the quantification of IP 25 as well as the sterols, see Fahl and Stein (2012). Accumulation rates of sea ice and phytoplankton biomarkers (IP 25 and brassicasterol, respectively) were calculated following Eq.…”
Section: Bartels Et Al: Atlantic Water Advection Vs Glacier Dynammentioning
confidence: 99%
“…The occurrence of floating ice could be revealed by the presence of ice-rafted debris (Lisitzin, 2002), while sea ice-related palaeo-productivity can be inferred from the sedimented remains of microscopic organisms and other biomarkers (Cronin et al, 2008). Recently, the determination of highly branched isoprenoids (IP 25 ) in specific sea ice diatoms have been proposed to describe the past sea ice variability (Vare et al, 2009;Fahl and Stein, 2012). Coastal records also help to understand the past dynamics of sea ice, producing a clear signal both in coastal sediment and landforms (Polyak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%